Efficacy (In Terms of Avoiding Hysterectomy) of the Triple P Procedure in Managing Morbidly Adherent Placenta - Mumtaz, Sadaf; Nighat Afridi; Salma Nisar; Hira Shafqat; Waseem Yousaf; Nafeesa Hiba (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the efficacy (in terms of avoiding hysterectomy) of the Triple P procedure in managing morbidly adherent placenta. Study Design: Case series. Place and Duration of the Study: Department of Obstetrics & Gynaecology, Combined Military Hospital, Peshawar Pakistan, from Dec 2018 to Mar 2020. Methodology: A total of 56 pregnant women of gestational age ≥32 weeks with the morbidly adherent placenta were included. Caesarean section was done in each patient by the consultant gynaecologist, and then the Triple P procedure was done. Efficacy in each patient was noted. Results: The mean age of the study participants was 30.79±4.42 years. In our analysis, the mean parity was 3.05±0.88. The mean number of caesarean sections was 2.00±1.11. The Triple P procedure was effective (in avoiding hysterectomy) in managing morbidly adherent placentas in 53(94.64 %) participants. Conclusion: This study concluded that the Triple P procedure’s efficacy (in terms of avoiding hysterectomy) in managing morbidly adherent placenta is very high.